X-ray spectroscopy applied to the study of the radiation transmission through nanomaterials - Künzel, Roseli; Okuno, Emico (Revista Brasileira de Física Médica, 2015)
In this study, we compare the energy absorbed by nanostructured and microstructured materials as a function of the x-ray beam energy and material concentration. For this purpose, we used CuO microparticles, with a mean particle size of about 56 μm, and nanoparticles with size in the range 10 – 100 nm. These particles were separately incorporated into a polymeric resin in proportions of 5% and 30% relative to the resin mass. Plates with about 5x5 cm² in area and uniform thickness were produced for each material. The x-ray generator was a Philips, model MG 450, with a tungsten anode tube. Measurements were performed for beams generated at 25, 40 and 100 kV tube voltages. Data were registered with an Amptek XR-100T-CdTe detector. Results show that nanostructured materials absorb more radiation than the microstructured ones for both material concentrations in the resin. For example, for a 5% particle concentration and material thickness of (6.0±0.2) mm, the difference between air kerma values is about 16% for 25 kV, 8% for 40 kV and about 2% for 100 kV.